1998
DOI: 10.1128/cdli.5.1.114-117.1998
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Neutralizing and Hemagglutination-Inhibiting Antibody Responses to Influenza A Virus Vaccination of Human Immunodeficiency Virus-Infected Individuals

Abstract: A neutralization enzyme immunoassay (N-EIA) was used to determine the neutralizing serum antibody titers to influenza A/Taiwan/1/86 (H1N1) and Beijing/353/89 (H3N2) viruses after vaccination of 51 human immunodeficiency virus (HIV) type 1-infected individuals and 10 healthy noninfected controls against influenza virus infection. Overall, the N-EIA titers correlated well with the hemagglutination-inhibition (HAI) titers that were observed in the same samples in a previous study (F. P. Kroon, J. T. van Dissel, J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Statistical data were generated using GraphPad Prism 5 software. HI titers were transformed into logarithmic values and statistical significance between groups was analyzed by one-way analysis of variance (ANOVA) with Newman-Keuls post-test [25].…”
Section: Discussionmentioning
confidence: 99%
“…Statistical data were generated using GraphPad Prism 5 software. HI titers were transformed into logarithmic values and statistical significance between groups was analyzed by one-way analysis of variance (ANOVA) with Newman-Keuls post-test [25].…”
Section: Discussionmentioning
confidence: 99%
“…Statistical data were generated using GraphPad Prism (version 5.03) software (GraphPad Software). Statistical significance between groups was determined by transforming HI titers into logarithmic values and performing one-way analysis of variance (ANOVA) with the Newman-Keuls posttest, as described previously (56). Normalized HI titers were compared by Dunn-corrected Kruskal-Wallis tests.…”
Section: Methodsmentioning
confidence: 99%
“…This assay therefore measures the functional capability of antibodies at a specific dilution, rather than just the total quantity. In settings of impaired host immunity, such as HIV infection, the VMN titer is more sensitive than the HI titer ( 12 ); VMN is also better for detecting antibodies to avian influenza viruses ( 13 ). Multiple studies have demonstrated good correlation between HI titers and VMN titers in pregnant women following monovalent H1N1 vaccination ( 14 , 15 ), and now seasonal influenza vaccination ( 16 ).…”
Section: Assessment Of Immunogenicitymentioning
confidence: 99%